2014
DOI: 10.1038/onc.2014.79
|View full text |Cite
|
Sign up to set email alerts
|

Semaphorin 3A upregulates FOXO 3a-dependent MelCAM expression leading to attenuation of breast tumor growth and angiogenesis

Abstract: Semaphorin 3A (Sema 3A), a member of semaphorin family, serves as a guidance clue during embryonic development and is known as a candidate tumor suppressor that attenuates breast tumor progression by binding with its co-receptor, neuropilin-1 (NRP-1). However, the underlying mechanism by which Sema 3A suppresses breast tumor growth is still unexplored. In this study, we report that Sema 3A regulates phosphorylation and nuclear translocation of phosphatase and tensin homolog (PTEN) and FOXO 3a. Moreover, Sema 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 56 publications
2
44
1
Order By: Relevance
“…Overexpression of PTEN and FOXO-3a enhances sema3A expression resulting in inhibition of breast cancer cells migration. 140 In agreement, it was reported that down regulation of sema3A expression by High mobility group box 1 (HMGB1), a chromatin-associated protein that aids in transcription and DNA repair that binds to the semaphorin 3A genomic locus and inhibits its expression, and as a result increases the migration of tumor cells. 141 Sema3A was also found to enhance the anti-angiogenic effects of VEGF receptor inhibitors such as DC101 and sunitinib.…”
Section: Semaphorins As Regulators Of Tumor Progressionsupporting
confidence: 48%
“…Overexpression of PTEN and FOXO-3a enhances sema3A expression resulting in inhibition of breast cancer cells migration. 140 In agreement, it was reported that down regulation of sema3A expression by High mobility group box 1 (HMGB1), a chromatin-associated protein that aids in transcription and DNA repair that binds to the semaphorin 3A genomic locus and inhibits its expression, and as a result increases the migration of tumor cells. 141 Sema3A was also found to enhance the anti-angiogenic effects of VEGF receptor inhibitors such as DC101 and sunitinib.…”
Section: Semaphorins As Regulators Of Tumor Progressionsupporting
confidence: 48%
“…One of the five genes, SEMA3A , was previously shown to exert a tumor suppressor function in breast cancer. One study reported that SEMA3A regulates phosphorylation of phosphatase and tensin homolog, which in turn activates a chain of TSGs to inhibit breast cancer growth, invasiveness and angiogenic capacity . Another study demonstrated a role for SEMA3A in proliferative control of tumor‐associated macrophages .…”
Section: Resultsmentioning
confidence: 99%
“…Among all genes containing CpG loci hypomethylated upon exposure to stilbenoids, we identified a group of 113 genes that lose methylation in both lowly MCF10CA1h and highly MCF10CA1a invasive breast cancer cells, and are associated with functions attenuating cancerous properties. One of the highest differences was located within SEMA3A , a gene found to have a potential tumor suppressor role in breast cancer . DNA hypomethylation of SEMA3A promoter as confirmed quantitatively by pyrosequencing coincided with increase in gene expression upon exposure to stilbenoids.…”
Section: Introductionmentioning
confidence: 82%
“…SEMA3A expression is downregulated with the increasing degree of malignancy in human breast cancer SEMA3A expression is downregulated in various human cancers, including epithelial ovarian, breast, gastric, and non-small cell lung cancer compared with the respective normal tissue (20)(21)(22)(23). Immunohistochemical staining of 83 breast cancer patient samples with varying grades of malignancy (grade I and III ductal breast cancer accounted for 39 patient samples) revealed that SEMA3A expression is significantly downregulated in grade III ductal breast carcinoma compared with grade I (Fig.…”
Section: Resultsmentioning
confidence: 99%